Challenging Misinformation: Exploring Limits and Approaches - Piccolo, Lara Schibelsky Godoy; Joshi, Somya; Karapanos, Evangelos; Farrell, Tracie (My University, 2019)
The manipulation of information and the dissemination of “fake news” are practices that trace back to the early records of human history. Significant changes in the technological environment enabling ubiquity, immediacy and considerable anonymity, have facilitated the spreading of misinformation in unforeseen ways, raising concerns around people’s (mis)perception of social issues worldwide. As a wicked problem, limiting the harm caused by misinformation goes beyond technical solutions, requiring also regulatory and behavioural changes. This workshop proposes to unpack the challenge at hand by bringing together diverse perspectives to the problem. Based on participatory design principles, it will challenge participants to critically reflect the limits of existing socio-technical approaches and co-create scenarios in which digital platforms support misinformation resilience.
Keywords: Co-creation; Disinformation; Fake news; Misinformation